Pemanfaatan Sistem Absensi Digital Terhadap Kedisiplinan Siswa: Studi Literatur dengan Pendekatan SPIDER - Benedictus Yoga Ardi Koswara; Mesta Limbong; Hotmaulina Sihotang (Jayapangus Press, 2026)
Student discipline remains a persistent challenge in school management, yet existing studies tend to focus on technical system development rather than its behavioral impact. This literature study addresses that gap by synthesizing research on the role of digital attendance systems in enhancing student discipline across formal educational settings. Using the SPIDER framework (Sample, Phenomenon of Interest, Design, Evaluation, Research Type), eight studies published between 2015 and 2025 were systematically selected and analyzed from Google Scholar. The synthesis reveals three consistent patterns: (1) digital attendance technologies including fingerprint biometrics, QR Code, RFID, and web-based applications significantly improved student punctuality and reduced absenteeism; (2) real-time parental notification features strengthened home-school supervision and reinforced disciplinary behavior; and (3) the effectiveness of these systems was contingent on non-technical factors, namely institutional commitment, consistent rule enforcement, and teacher modeling. These findings contribute to the data-driven school management literature by demonstrating that digital attendance functions not merely as an administrative tool but as a behavioral intervention instrument. Schools are advised to integrate digital attendance data into character development programs to maximize disciplinary outcomes.